Swamp thing. The complete series [videorecording (DVD)] - Reed, Crystal, 1985-; Madsen, Virginia, 1961-; Bean, Andy; Mears, Derek; Wade, Henderson; Sten, Maria (Actor); Prescott, Jeryl; Patton, Will; Beals, Jennifer; Durand, Kevin; Ziering, Ian, 1964-; Beach, Michael (Warner Bros., 2020)
Dr. Abby Arcane is investigating a deadly swamp-born virus in a small town in Louisiana. When a mysterious creature emerges from the murky marsh, she finds herself facing the nightmares of a supernatural world where no one is safe. With nature wildly out of balance and coming for the people of Marais, in the end, it may take some Thing from the swamp to save it.